Regulating the Polarization of Macrophages: A Promising Approach to Vascular Dermatosis - Huiling Peng; Dehai Xian; Jiexiong Liu; Shihong Pan; Ran Tang; Jianqiao Zhong (Journal of Immunology Research)
Macrophages, a kind of innate immune cells, derive from monocytes in circulation and play a crucial role in the innate and adaptive immunity. Under the stimulation of the signals from local microenvironment, macrophages generally tend to differentiate into two main functional phenotypes depending on their high plasticity and heterogeneity, namely, classically activated macrophage (M1) and alternatively activated macrophage (M2). This phenomenon is often called macrophage polarization. In pathological conditions, chronic persistent inflammation could induce an aberrant response of macrophage and cause a shift in their phenotypes. Moreover, this shift would result in the alteration of macrophage polarization in some vascular dermatoses; e.g., an increase in proinflammatory M1 emerges from Behcet’s disease (BD), psoriasis, and systemic lupus erythematosus (SLE), whereas an enhancement in anti-inflammatory M2 appears in infantile hemangioma (IH). Individual polarized phenotypes and their complicated cytokine networks may crucially mediate in the pathological processes of some vascular diseases (vascular dermatosis in particular) by activation of T cell subsets (such as Th1, Th2, Th17, and Treg cells), deterioration of oxidative stress damage, and induction of angiogenesis, but the specific mechanism remains ambiguous. Therefore, in this review, we discuss the possible role of macrophage polarization in the pathological processes of vascular skin diseases. In addition, it is proposed that regulation of macrophage polarization may become a potential strategy for controlling these disorders.